Formation of children's health on the example of Zaporozhye - Kravchenko, H. V.; Boyko, Ya. A.; Podolyak, M. V. (Запорізький державний медико-фармацевтичний університет, 2023)
The aim of the study. To study and rate the quality of pupils’ lives social conditions of a large industrial city (for example Zaporizhzhia city).
Keywords: тези доповідей